Defining the practice of pancreatoduodenectomy around the world. Issue 12 (16th September 2015) - McMillan, Matthew T.; Malleo, Giuseppe; Bassi, Claudio; Sprys, Michael H.; Vollmer, Charles M.
Abstract: Background: Pancreatoduodenectomy (PD) is a technically challenging operation characterized by numerous management decisions. Objective: This study was designed to test the hypothesis that there is significant variation in the contemporary global practice of PD. Methods: A survey with native‐language translation was distributed to members of 22 international gastrointestinal surgical societies. Practice patterns and surgical decision making for PD were assessed. Regions were categorized as North America, South/Central America, Asia/Australia, and Europe/Africa/Middle East. Results: Surveys were completed by 897 surgeons, representing six continents and eight languages. The median age and length of experience of respondents were 45 years and 13 years, respectively. In 2013, surgeons performed a median of 12 PDs and reported a median career total of 80 PDs; only 53.8% of respondents had surpassed the number of PDs considered necessary to surmount the learning curve (>60). Significant regional differences were observed in annual and career PD volumes ( P < 0.001). Only 3.7% of respondents practised pancreas surgery exclusively, but 54.8% performed only hepatopancreatobiliary surgery. Worldwide, the preferred form of anastomotic reconstruction was pancreatojejunostomy (88.7%). Regional variability was evident in terms of anastomotic/suture technique, stent use and drain use (including type and number), as well as in the use of octreotide, sealants and autologous patches ( P < 0.02 for all). Conclusions: Globally, there is significant variability in the practice of PD. Many of these choices contrast with established randomized evidence and may contribute to variance in outcomes.